Islamic Finance, Halal Ecosystem, Financial Inclusion and SME Growth in Nigeria - Ibrahim Ayodele Yusuf; Jamiu Adeniyi Yusuf; Azeem Tunde Muhammed; Ismail Aderole Ayuba (Universitas Pembangunan Nasional Veteran Jakarta, 2026)
Abstract This study investigates the integration of Islamic finance within Nigeria's halal business ecosystem and its subsequent impact on financial inclusion and Small and Medium Enterprise (SME) growth. Utilizing a quantitative methodology, the researchers applied Structural Equation Modeling (SEM) to survey data from 312 participants, including SME stakeholders and Islamic finance consumers. The empirical results demonstrate that Islamic finance significantly enhances financial inclusion by providing non-interest financial alternatives to previously marginalized populations. Simultaneously, the halal business ecosystem serves as a vital catalyst for both inclusion and SME expansion by fostering a structured environment built on trust, standardization, and increased market access. Notably, the study confirms that financial inclusion acts as a robust driver of enterprise development and partially mediates the relationship between Islamic finance and SME growth. This suggests that Islamic finance benefits businesses both through direct funding and the indirect facilitation of broader financial access. The study concludes that the synergetic integration of Islamic finance and the halal economy is essential for sustainable development in Nigeria. Key recommendations include strengthening Shariah-compliant institutions, establishing a rigorous national halal certification framework, improving financial literacy, and enhancing institutional coordination to maximize the economic potential of these sectors.